Metadata Standards for Semantic Interoperability in Electronic Government - Davies, J; Harris, S; Crichton, C; Shukla, A; Gibbons, J (Cairo, 2008)
Effective data sharing, across government agencies and other organisations, relies upon agreed meanings and representations.  A key, technological challenge in electronic governance is to ensure that the meaning of data items is accurately recorded, and accessible in an economical—effectively, automatic—fashion.  In response, a variety of data and metadata standards have been put forward: from government departments, from industry groups, and from organisations such as the ISO and W3C. This paper shows how the leading standard for metadata registration—ISO11179—can be deployed without the need for a single, monolithic conceptualisation of the domain, and hence without the need for universal agreement upon a particular model of electronic governance.  The advantages of this approach are discussed with regard to the UK eGovernment Interoperability Framework (eGIF) and the UK Integrated Public Sector Vocabulary (IPSV).